An automated entities extraction model for elements recognition from the structural 2D drawing - Mohd Zaimi A. M., author; Chitrakala M., author; Abdul Hakkim Mohamad, author; Fifth International Conference in the 21th Century (CII-V) "Collaboration and Integration in Engineering Management and Techonology May 20-22 5th : 2009 : Istanbul, Turkey) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL